Why Preserve Natural Variety? - Norton, Bryan G. (Studies in moral, political, and legal philosophy., 2014)
A valuable and unique contribution both to environmental ethics and public policy analysis of the preservation of species question. Norton provides a critical overview of the range of thought on the issue, presents a new and comprehensive rationale for preservation of both species and ecosystems, and addresses policy issues. Originally published in 1990. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserv.